2010
DOI: 10.1167/iovs.09-3710
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal Hormone Therapy Increases Retinal Blood Flow and Protects the Retinal Nerve Fiber Layer

Abstract: These findings indicate that estrogens and HT increase retinal blood flow and protect the retinal nerve fiber layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 85 publications
0
75
0
Order By: Relevance
“…27 Estrogen has also been shown to increase retinal blood flow and protect the RNFL in animal and clinical models of optic nerve injury. 28 In an experimental model of Leber hereditary optic neuropathy, 17␤-estradiol activated mitochondrial biogenesis and improved energetic competence, prompting the authors to postulate that the protective effects of estrogen may explain the higher prevalence of Leber hereditary optic neuropathy in men relative to women. 29 Although it is plausible that the neuroprotective benefits of estrogen may have contributed to the relatively wellpreserved RNFL values in women relative to men observed in this study, we did not specifically evaluate sex hormones and therefore cannot draw any conclusions in this regard.…”
Section: Figure 2 Change In Retinal Nerve Fiber Layer (Rnfl) Thicknesmentioning
confidence: 99%
“…27 Estrogen has also been shown to increase retinal blood flow and protect the RNFL in animal and clinical models of optic nerve injury. 28 In an experimental model of Leber hereditary optic neuropathy, 17␤-estradiol activated mitochondrial biogenesis and improved energetic competence, prompting the authors to postulate that the protective effects of estrogen may explain the higher prevalence of Leber hereditary optic neuropathy in men relative to women. 29 Although it is plausible that the neuroprotective benefits of estrogen may have contributed to the relatively wellpreserved RNFL values in women relative to men observed in this study, we did not specifically evaluate sex hormones and therefore cannot draw any conclusions in this regard.…”
Section: Figure 2 Change In Retinal Nerve Fiber Layer (Rnfl) Thicknesmentioning
confidence: 99%
“…(11,12). Additionally, animal models and clinical studies have shown that the perfusion of the optic nerve, retinal ganglion cells, and their supporting structures are increased by estradiol (13)(14)(15). Finally, estradiol has neuroprotective effect which appears to be mediated at least in part through estrogen receptors in the retinal ganglion cells in glaucoma animal models (4,13).…”
Section: Discussionmentioning
confidence: 99%
“…A recent example of the impact of estrogen on nerve tissue is seen in the retinal arterial blood flow in continuous HT users versus never users. Deschenes et al 24 concluded that Bestrogens and HT increase retinal blood flow and protect the retinal nerve layer. [ In ovariectomized rats, BE 2 treatment significantly increased retinal perfusionI.…”
Section: Discussionmentioning
confidence: 99%